2013
DOI: 10.1007/s11067-013-9198-2
|View full text |Cite
|
Sign up to set email alerts
|

Model Representation & Decision-Making in an Ever-Changing World: The Role of Stochastic Process Models of Transportation Systems

Abstract: We review and advance the state-of-the-art in the modelling of transportation systems as a stochastic process. The conceptual and theoretical basis of the approach is explained in detail. A variety of examples are given to motivate its use in the field. While the examples cover a wide range of modelling philosophies, in order to provide focus they are restricted to modelling a special class of problems involving driver route choice in networks. Our overall objective is to establish the applicability of this ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…There has been a substantial stream of development of day-to-day dynamic models to look into the variation of traffic flows from epoch to epoch (Cascetta, 1989;Watling and Cantarella, 2015). It is believed that travelers'…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…There has been a substantial stream of development of day-to-day dynamic models to look into the variation of traffic flows from epoch to epoch (Cascetta, 1989;Watling and Cantarella, 2015). It is believed that travelers'…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…DPs also allow transitions to be examined especially when some shock or designed change occurs He & Liu, 2012. A recent review and synthesis of DP models in discrete and continuous time may be found in Cantarella & Watling 2015; in this paper no comparison is carried out with DPs in continuous time and/or based on Wardrop approach to route choice behaviour for a recent paper see Guo et al, 2015, since results obtained with these models can hardly transferred to the kind of models discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In a companion paper, we have provided a similar treatment of stochastic process models, which emerge from a quite different theoretical backdrop (Watling & Cantarella, 2013a). Together, these papers extend and update the treatment of these two kinds of modelling approach as described in the unifying framework of Cantarella & Cascetta (1995).…”
Section: Discussionmentioning
confidence: 94%
“…In the present paper we consider the modelling of road transport systems as a deterministic process (stochastic process models are widely discussed in Watling & Cantarella, 2013a, 2013b. The main contribution is to present a unified treatment of discrete-time and continuous-time approaches, these two classes of approach having been developed in two parallel streams of research which have had little connection made between them.…”
Section: Ejtl-d-12-00064r2 Pagementioning
confidence: 99%